Antiretroviral Efficacy and Pharmacokinetics of Oral Bis(isopropyloxycarbonyloxymethyl)9-(2-Phosphonylmethoxypropyl)adenine in Mice - Naesens, Lieve (American Society for Microbiology, 1998)
To overcome the low oral bioavailability of the highly potent and selective antiretroviral agent (R)-9-(2-phosphonylmethoxypropyl)adenine (PMPA), a new lipophilic ester derivative, i.e., the bis(isopropyloxycarbonyloxymethyl)-ester [bis(POC)-PMPA], was prepared. The usefulness of bis(POC)-PMPA as an oral prodrug for PMPA was investigated in the intestinal mucosa Caco-2 cell monolayer model. The total transport of bis(POC)-PMPA was 2.7%, whereas it was less than 0.1% for PMPA. Bis(POC)-PMPA was considerably metabolized inside the epithelial cells, since the majority of the compound was recovered after transport in the form of the monoester metabolite [mono(POC)-PMPA]. In contrast, bis(POC)-PMPA was relatively resistant to degradation at the luminal side of the Caco-2 cells. Pharmacokinetic studies with mice showed that the oral bioavailability of bis(POC)-PMPA (calculated from the curves of the concentration of free PMPA in plasma) was 20%. Neither bis(POC)-PMPA nor mono(POC)-PMPA could be recovered in plasma, suggesting the efficient release of the active drug PMPA after oral administration of bis(POC)-PMPA. Severe combined immunodeficient (SCID) mice infected with Moloney murine sarcoma virus (MSV) and treated orally with bis(POC)-PMPA for 5 or 10 days (dosages, 50, 100, or 200 mg of PMPA equivalent per kg of body weight per day) showed a significant delay in MSV-induced tumor appearance and tumor-associated death. The antiviral efficacy of oral bis(POC)-PMPA was related to the dosage and treatment period and was not significantly different from that of subcutaneous PMPA given at an equivalent dose. The favorable pharmacokinetic profile, marked antiviral efficacy, and low toxicity make bis(POC)-PMPA an attractive oral prodrug of PMPA that should be further pursued in clinical studies with patients infected with human immunodeficiency virus or hepatitis B virus.